2016
DOI: 10.1007/s00393-016-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin, the angiogenic and mitogenic growth factor: levels in serum and synovial fluid in rheumatoid arthritis and osteoarthritis

Abstract: Our results point to a possible important role of PTN in RA and OA. We firstly report a serological pattern of PTN in the sera and synovial fluids of RA patients. However its implementation as a disease marker or a potential target therapy in both diseases awaits larger studies and further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…PTN is a heparin-binding growth factor, with potent mitogenic and angiogenic activity, and a crucial regulator of cancer metastasis, bone development, and bone repair (Liedert et al, 2014). Previous studies have reported that PTN levels are increased in the serum, chondrocytes, and subchondral bone of patients with OA, indicating that PTN might be a crucial factor during disease progression (Kaspiris et al, 2013;Fadda et al, 2018). PTN also promotes endothelial cell proliferation and migration and induces angiogenesis by interacting with two main receptors, PTPRZ and αVβ3 (Fukada et al, 2006;Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…PTN is a heparin-binding growth factor, with potent mitogenic and angiogenic activity, and a crucial regulator of cancer metastasis, bone development, and bone repair (Liedert et al, 2014). Previous studies have reported that PTN levels are increased in the serum, chondrocytes, and subchondral bone of patients with OA, indicating that PTN might be a crucial factor during disease progression (Kaspiris et al, 2013;Fadda et al, 2018). PTN also promotes endothelial cell proliferation and migration and induces angiogenesis by interacting with two main receptors, PTPRZ and αVβ3 (Fukada et al, 2006;Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MK and PTN were also shown to be associated with autoimmune diseases such as RA [10,11], MS [12,13], cancers [2,9], and the inhibition of HIV infection [14][15][16]. Therefore, assessing the production of MK and PTN by innate APCs in these situations and regulating their production by these cells is potentially important for the better management of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MK and PTN were also shown to be associated with different diseases, including cancers [2,9] and autoimmune diseases such as rheumatoid arthritis (RA) [10,11], systemic lupus erythematosus (SLE) [3], and multiple sclerosis (MS) [12,13]. We and others have shown that MK and PTN binding to their receptors can inhibit HIV infection by interfering with the capacity of the virus to bind to target cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%